Periscapular Strength Profile Changes in Collegiate Baseball Pitchers Over the Course of a Season - Patrick S Pabian; Victoria Roach; Roselin Howard; Lauren Johnston; Ryan McGuire (North American Sports Medicine Institute, 2024)
# Background Repetitive application of high forces to the shoulder and scapular musculature during the pitching motion over the course of a collegiate baseball season may lead to changes in strength and increased fatigue, potentially predisposing pitching athletes to injury. The purpose of this study was to investigate periscapular strength profiles of Division I collegiate baseball players over the course of a season. # Methods This study was a retrospective data analysis of 18 Division I baseball pitchers. Isometric scapular plane abduction (scaption), external rotator, internal rotator, middle trapezius, and lower trapezius isometric strength was measured on throwing arm of each subject using a MicroFET 2 handheld dynamometer. Data were collected in a single session at the preseason, midseason, and postseason of the college baseball season, which spanned a five-month period. A repeated measures ANOVA was utilized to determine if there was a significant change in periscapular strength across the baseball season. # Results Over the three time-points, all strength values decreased for each muscle group, with decreases ranging from 3-14%. Changes in scaption strength values were statistically significant (p=0.018, partial eta squared =0.284) with an 8% reduction over the entire season, specifically with a 5% decline from mid-season to post-season. While external rotator, internal rotator, middle trapezius, and lower trapezius strength values all decreased over the course of the season (range 0.02kg to 1.8kg), these differences were not statistically significant. However, the middle trapezius strength value change (1.3kg loss) exceeded the minimal detectible change. # Conclusion Periscapular muscles in baseball pitchers diminish in strength over the course of a collegiate baseball season. Understanding strength changes over the course of a season may influence training and therapeutic interventions. # Level of Evidence 3b